Injil dan Pluralitas Budaya Asia: Studi Narator Matius 28:19-20 - Harming Harming; Alex Stefanus Ginting; Samuel Abdi Hu; Nosita Br. Tarigan (Sabda: Jurnal Teologi Kristen, 2025)
This study analyzes the narrative of Matthew 28:19-20—known as the Great Commission—in the context of Asian cultural plurality using a translational model and narrative hermeneutic approach. The main focus of the research is how gospel texts can be translated and interpreted in a relevant and contextual way in the midst of the diversity of cultures, languages, and traditions in Asia. Through qualitative methods and document analysis, this study identifies the importance of understanding local cultures, contextualizing the gospel message, and the role of the church in building cross-cultural dialogue. The results of the study show that effective discipleship and evangelism require collective community involvement, adaptation to the challenges of the digital age, and a reinterpretation of the dimensions of baptism and teaching to remain relevant to the needs of modern society. This research recommends inclusive and adaptive evangelistic strategies, and emphasizes the importance of building intercultural relationships of mutual respect to realize the church's universal and contextual mission. Abstrak:Penelitian ini menganalisis narasi Matius 28:19-20-yang dikenal sebagai Amanat Agung-dalam konteks pluralitas budaya Asia dengan menggunakan pendekatan model translasi dan hermeneutik naratif. Fokus utama penelitian adalah bagaimana teks Injil dapat diterjemahkan dan diinterpretasikan secara relevan dan kontekstual di tengah keragaman budaya, bahasa, dan tradisi di Asia. Melalui metode kualitatif dan analisis dokumen, penelitian ini mengidentifikasi pentingnya pemahaman budaya lokal, kontekstualisasi pesan Injil, serta peran gereja dalam membangun dialog lintas budaya. Hasil penelitian menunjukkan bahwa pemuridan dan penginjilan yang efektif memerlukan keterlibatan komunitas secara kolektif, adaptasi terhadap tantangan era digital, serta pemaknaan ulang dimensi baptisan dan pengajaran agar tetap relevan dengan kebutuhan masyarakat modern. Penelitian ini merekomendasikan strategi penginjilan yang inklusif dan adaptif, serta menekankan pentingnya membangun hubungan saling menghargai antarbudaya untuk mewujudkan misi gereja yang universal dan kontekstual.Kata Kunci: Injil, Matius, penginjilan, gereja.